Kemiskinan dan Anak yang Memerlukan Perlindungan Khusus - Anwar Sitepu (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2014)
This paper is written to analyze whether poverty is contributing to the problem of children who need special protection and how the poverty makes children suffer until the extent to require special protection. The analyzed data are cases of 25 children who have received special protection from five Children Protection House (RPSA) in Indonesia. These cases are the result of research that is conducted by Central of Research and Development of Social Welfare, Puslitbang Kesos, in 2011 to evaluate the Children’s Social Protection Program through the Children Protection House (RSPA). An analysis of the poverty factor in the case of children who need special protection is very important, considering that in previous research the poverty factor have not been explored yet. While in every case of the research on those chlidren, it indicates that poverty is the root of the problem faced by almost all children. From the case of 25 children turn out that 24 children (96%) are caming from poor family. Poverty makes children suffer-need special protection-through two patterns. First, poverty undermines the family unity, to transfer children’s nurture from biological family to other party. Second, poverty makes families fail to meet the needs of children. First or second pattern leads to suffer children. Children become victims, neglected or being neglected, exploited sexually and or economically, physical violence and emotional pressure until they leave for and live in the street.